A Significant Association Between rs2295190 Polymorphism of the ESR1 Gene and Fibromyalgia Syndrome: ESR 1 Polymorphism in Fibromyalgia Syndrome - Kaydok, Ercan; Ozmen, Esma; Sari, Ismail; Cakıroglu, Gozde Sen; Tas, Ayca; Silig, Yavuz; Hayta, Emrullah (Cellular and Molecular Biology, 2022)
Fibromyalgia syndrome (FMS) is a multifactorial disease characterized by chronic diffuse pain. Genetic factors are also involved in the etiology. However, there is not enough information on the genetic factors that play a role in the pathogenesis of FMS. The aim of this study is to investigate the relationship between estrogen receptor 1 gene (ESR1) 594G>A (rs2228480) and 325C>G (rs2295190) polymorphisms and fibromyalgia syndrome (FMS). A total of 294 women, 146 of who were FMS patients and 148 of whom were healthy controls, were enrolled in the study. The instruments used to collect data from patients included patient follow-up form, Visual Analogue Scale (VAS), and Fibromyalgia Impact Questionnaire (FIQ). Genotyping of ESR1 594G>A and 325C>G polymorphisms in the extracted DNA samples was performed using an RT-PCR device and TaqMan hydrolysis probes. It was found that, for rs2295190 polymorphism, patients with CG and GG genotypes versus CC genotypes showed a decreased risk for FMS (OR: 0.442; 95% CI: 0.234-0.833). But there were no significant differences were found in the genotype distribution of rs2228480 polymorphism between the FMS patients and controls. The intragroup evaluation of FMS patients revealed no significant association between symptoms, pain score, FIQ score, and polymorphisms (p>0.05). We are of the opinion that there is a significant association between ESR1 rs2295190 polymorphism and FMS and that this polymorphism may be protective against FMS. However, there is a need for comprehensive studies on different populations to obtain clearer data as well as further studies to elucidate the possible mechanism of association.